The causal relationship between multiple autoimmune diseases and nasal polyps - Chen, Siyuan; Tan, Lu; Qin, Danxue; Lv, Hao; Liu, Kunyu; Xu, Yingying; Wu, Xiaomin; Huang, Jingyu; Xu, Yu (Frontiers in Immunology, 2023)
Background Although previous sporadic studies have reported the associations between a few autoimmune diseases and nasal polyps, these studies have limitations such as conflicting results, small sample sizes, and low levels of evidence. Methods Several autoimmune diseases were selected as exposures while the nasal polyps were selected as outcomes. Bidirectional univariable Mendelian randomization and multivariable Mendelian randomization analyses were performed after rigorous screening of instrumental variables. Then mediation analyses were conducted to further investigate the underlying mechanisms. Results For the first time, we investigated the causal relationships between nine autoimmune diseases and nasal polyps in different genders and found: (1) there was a causal association between adult-onset Still's disease and nasal polyps; (2) sarcoidosis, ulcerative colitis, type 1 diabetes, and Crohn’s disease had no significant associations with nasal polyps; (3) celiac disease showed a suggestive positive association with female nasal polyps, whereas juvenile arthritis and multiple sclerosis showed suggestive positive associations with male nasal polyps. By contrast, arthropathic psoriasis showed a suggestive negative association with nasal polyps. In addition to these nine diseases, previous controversial issues were further investigated: (1) there was a causal relationship between rheumatoid arthritis and nasal polyps, which was partially mediated by “BAFF-R for IgD+ B cells”; (2) ankylosing spondylitis showed suggestive positive associations with the female but not the male nasal polyps. Besides, we validated that there was no causal effect of autoimmune hyperthyroidism on nasal polyps. Conclusion Specific conclusions regarding the causal effects of multiple autoimmune diseases on nasal polyps are the same as above. By comparing results between different genders, we have initially observed the sex bimodality in the causal effects between autoimmune diseases and nasal polyps, with those on male nasal polyps being stronger than those on female nasal polyps. Our study lays a solid foundation for further research in the future, not only helping identify individuals susceptible to nasal polyps early but also improving our understanding of the immunopathogenesis of these heterogeneous diseases.